2011
DOI: 10.1016/j.neuron.2011.06.028
|View full text |Cite
|
Sign up to set email alerts
|

The Sound of Silence: Ionic Mechanisms Encoding Sound Termination

Abstract: Offset responses upon termination of a stimulus are crucial for perceptual grouping and gap detection. These gaps are key features of vocal communication, but an ionic mechanism capable of generating fast offsets from auditory stimuli has proven elusive. Offset firing arises in the brainstem superior paraolivary nucleus (SPN), which receives powerful inhibition during sound and converts this into precise action potential (AP) firing upon sound termination. Whole-cell patch recording in vitro showed that offset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(164 citation statements)
references
References 60 publications
8
156
0
Order By: Relevance
“…In neurons of the brainstem superior paraolivary nucleus (SPN), this IPSP–HCN‐driven increase in firing encodes sound termination (Kopp‐Scheinpflug et al . 2011). The relationship between inhibition and I h is even more complex considering that I h contributes to a depolarization of the resting membrane potential that maintains the driving force for Cl − ions (Pavlov et al .…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
“…In neurons of the brainstem superior paraolivary nucleus (SPN), this IPSP–HCN‐driven increase in firing encodes sound termination (Kopp‐Scheinpflug et al . 2011). The relationship between inhibition and I h is even more complex considering that I h contributes to a depolarization of the resting membrane potential that maintains the driving force for Cl − ions (Pavlov et al .…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
“…The membrane time constant of an in vivo neuron is a complex function of multiple ion currents (e.g., K ϩ ) (Rothman and Manis, 2003) and nonspecific, hyperpolarization-activated currents (e.g., I h ) (Kopp-Scheinpflug et al, 2011); however, our simplified model allowed us to easily set the passive membrane time constant by altering the maximum conductance of passive leak channels (g leak ). In the default model with g leak ϭ 0.25 mS/ cm 2 (i.e., r leak ϭ 4000 ⍀cm 2 ) and c m ϭ 1.0 F/cm 2 , the membrane time constant was ϭ 4 ms.…”
Section: Membrane Time Constantmentioning
confidence: 99%
“…This tendency is applied to bats such as Rhinolophus megaphyllus, Rhinolophus philippinensis, Hipposideros diadema, Taphazous georgianu [52], Aseuiscus tricuspidatus [48], guinea pigs [24], rats [51], mice [31], as well as humans [53], but independent of recording methods. Using AEP recording, compared with the amplitude of onset response increasing monotonically with intensity elevation, the amplitude of offset ABR goes through a maximum [48], sometimes will reduce with further increase of stimulus intensity [54], while the number of action potentials (APs) continuously increases with sound intensity increasing in the superior paraolivary nucleus (SPON) of mice using single-unit recording [40], this discrepancy may be induced by the recording methods or the difference between nuclei because the ABR amplitude depend on the synchronization of neuron population and some neurons may change their discharge patterns with intensity changing. He [20] also demonstrated that most of the onset-offset neurons in MGB of guinea pig changed to either onset or offset response as the stimulus changes.…”
Section: Stimulus Intensity Dependencementioning
confidence: 99%
“…Koop-Scheinpflug et al [40] [68,89]. Given that cells within the ventral nucleus of the lateral lemniscus (VNLL) respond to tones with a single precise onset response [90,91], and that SPON and VNLL neurons are respectively GABAergic and glycinergic, and both provide inhibition to the ipsilateral IC [92,93], the convergent inputs from SPON and VNLL to IC may explain the onset-offset responses with IPSPs both at the onset and offset of the tone in the auditory midbrain [94][95][96].…”
Section: Intrinsic Conductance Properties Of Offset Neuron Membranesmentioning
confidence: 99%
See 1 more Smart Citation